Ecology and Environmental Science Waste Problems and Biota Life - Nur Efendi; Hedsing Cressendo; Sri Eka Putri; Yasmi Antara; Wahyu Prasetyo Agus Susanto; Musharyanto Musharyanto; Era Setiawan; Hendriyanto Hendriyanto; Fachrul Latuconsina; Rachma Delli Fachrin; Abdul Razak; Eri Barlian; Nurhasan Syah; Skunda Diliarosa (Science and Environmental Journal for Postgraduate, 2021)
The volume of waste generated due to human activities is strongly influenced by the rate of population growth. The amount of waste created in an area is proportional to the number of residents from various types of activities, and the number of material goods consumed by the community. The environmental issue that currently has no doubt is that waste management is still far from adequate. The rate of population growth has a significant impact on the amount of waste generated by human activities. There is still a low level of human awareness of the bad effects caused by waste. Indiscriminate disposal of garbage and not being managed properly will cause big problems because throwing garbage in the open will result in soil pollution which will also have an impact on groundwater and air channels. The seriousness and need for waste management begin to be studied from upstream (waste source) to downstream (final disposal site) with the application of ideas such as 3R to 5R, but in the community, more emphasis is placed on the 3R priority, Reuse, Reduce, and, Recycle. The disposal of plastic waste is one of the contaminants that harm marine life. Not only threatening the terrestrial environment, waste pollution that is not managed properly can also have an impact on the marine biota environment because waste that ends up in the sea is the result of land waste. About 10% of all new plastic that will be produced will be waste going into rivers and ending up in the ocean. Marine debris, especially inorganic waste, is the main enemy that will not decrease and its existence will continue to be avoided. In this case, community participation is necessary to create a healthy living environment. Everyone from the community and the community has the same rights, obligations, and roles in environmental management, regardless of rural, remote, or urban communities, because the scope is not only in certain places but throughout the Unitary State of the Republic of Indonesia.